Positive electrode for lithium-sulfur battery and method of manufacturing same
Patent Information
- Application Number
- JP2022533199
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-01
- Filing Date
- 2021-06-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-06-30
AI Technical Summary
【0024】 本発明によるリチウム‐硫黄電池用正極は優れる表面特性によって凹凸が小さくて負極の不均一な成長及びデンドライト形成を防ぐことができるし、正極活物質の間のブリッジ(Bridge)形態の構造によって優れる接着力を効果として持つ。
Smart Images

Figure 0007631344000005 
Figure 0007631344000006 
Figure 0007631344000007
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2020-0080757, filed July 1, 2020, and the entire contents of the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a positive electrode for a lithium-sulfur battery and a method for making the same. [Background technology]
[0003] As the range of secondary battery applications expands from small portable electronic devices to medium and large electric vehicles (EVs), energy storage systems (ESSs), electric ships, etc., the demand for lithium secondary batteries with high capacity, high energy density and long life is rapidly increasing.
[0004] Among them, lithium-sulfur batteries refer to a battery system that uses a sulfur-based material with a "S-S bond (Sulfur-Sulfur Bond)" as the positive electrode active material and lithium metal as the negative electrode active material. Sulfur, the main material of the positive electrode active material, has a low weight per unit atom, is abundant, easy to supply and demand, and is inexpensive, which helps reduce the unit cost of battery production, and is environmentally friendly as it is non-toxic.
[0005] In particular, lithium-sulfur batteries have a theoretical discharge capacity of 1,675mAh / g-sulfur and can theoretically realize a high energy storage density of 2,600Wh / kg relative to weight. This is a much higher value than the theoretical energy density of other battery systems currently being researched (Ni-MH battery: 450Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO2 battery: 1,000Wh / kg, Na-S battery: 800Wh / kg) and lithium-ion batteries (250Wh / kg), and is therefore attracting much attention in the medium- and large-sized secondary battery market that has been developed so far.
[0006] The lithium-sulfur battery has a positive electrode, a negative electrode, a separator, and an electrolyte as basic components, and the positive electrode is the main component of the lithium-sulfur battery in that the positive electrode active material has a large effect on the battery performance. The positive electrode can be manufactured by first adding a binder and a solvent to the positive electrode active material to prepare a positive electrode active material slurry having a fluidity, and then coating the slurry on a current collector and drying it.
[0007] However, in the past, the manufacturing of positive electrodes for lithium-sulfur batteries involved the use of positive active material slurries that were fluid, i.e. had a low solid content, which meant that the process of coating with coating equipment and then drying by heating took a long time, slowing down the production speed of the positive electrode. To overcome this, attempts were made to use positive active material slurries with high solid content, but slurries with high solid content did not flow well, making it difficult to manufacture electrodes using the existing coating process.
[0008] Furthermore, with regard to the preparation of the positive electrode active material slurry, the prior art (paper) Science Advances, 03 Jan 2020: Vol. 6, no. 1, eaay2757. discloses that in the case of a method of preparing a slurry by adding water to a mixture of a sulfur / carbon composite and a binder in a dry state, web-like bridging bonds or ribbon-like bridging bonds are formed between the positive electrode active materials during the preparation of the positive electrode, thereby increasing the binding force between the active material particles.
[0009] The prior art documents disclose the bonding structure characteristics between positive electrode active material particles by a slurry preparation method, but do not disclose a specific solid content concentration of the positive electrode active material that can further improve the bonding strength. As a result, they have limitations in that they do not disclose a method for manufacturing a positive electrode using a slurry having a high solid content concentration that does not have flowability.
[0010] Therefore, there is a need for research and development of a positive electrode for a lithium-sulfur battery and a manufacturing method thereof that can improve the binding strength between the positive electrode active materials, the surface characteristics of the positive electrode, and the capacity and stability of the battery while increasing the production speed and making the process more efficient by shortening the time of the positive electrode drying process of the lithium-sulfur battery. [Prior art documents] [Non-patent literature]
[0011] [Non-Patent Document 1] (Paper 1)Science Advances, 03 Jan 2020:Vol.6, no.1, eaay2757. Summary of the Invention [Problem to be solved by the invention]
[0012] In order to solve the above problems, the present inventors have studied the application of a pressing process using a roll press during the manufacture of a positive electrode using a positive electrode active material slurry having a high solid content that is not flowable, and have completed the present invention.
[0013] Therefore, an object of the present invention is to provide a method for manufacturing a positive electrode for a lithium-sulfur battery, which can reduce the cost of the drying process and improve the production speed by shortening the drying time of the positive electrode manufacturing process, and also to provide a positive electrode for a lithium-sulfur battery, which can improve the adhesive strength of the positive electrode through cross-linking between positive electrode active materials having a high solid content, and can reduce the unevenness of the positive electrode surface to improve surface characteristics and battery stability, and a method for manufacturing the same. [Means for solving the problem]
[0014] According to a first aspect of the present invention, A positive electrode for a lithium-sulfur battery comprising: a current collector; and a positive electrode active material layer formed on at least one surface of the current collector; the positive electrode active material layer comprises a positive electrode active material and a binder, and the positive electrode active material layer is a (arithmetic mean surface roughness of positive electrode), S z(i) 1μm≦S a ≦5μm(ii)10μm≦S z ≦60μm (S a is the average distance from the middle surface of the uneven structure on the positive electrode surface to the highest and lowest points of each uneven portion, and z means the distance from the lowest point to the highest point on the positive electrode), to provide a positive electrode for a lithium-sulfur battery.
[0015] In one embodiment of the present invention, the adhesive strength between the current collector and the positive electrode active material layer is 6.5 to 9.5 gf / cm.
[0016] In one embodiment of the present invention, the porosity of the positive electrode is 50 to 80%.
[0017] In one embodiment of the present invention, the sulfur loading of the positive electrode is 1 to 10 mAh / cm 2 It is.
[0018] In an embodiment of the present invention, the positive electrode active material may include a material selected from the group consisting of elemental sulfur, a sulfur-based compound, a sulfur-carbon composite, and combinations thereof.
[0019] According to a second aspect of the present invention, The present invention provides a method for manufacturing a positive electrode for a lithium-sulfur battery, comprising the steps of: (1) mixing a sulfur-carbon composite and a binder, and then adding water to prepare a positive electrode active material slurry; (2) placing the positive electrode active material slurry on a current collector, and covering it with a release film to prepare a structure in the order of current collector-slurry-release film; (3) compressing the structure using a roll press; (4) removing the release film from the compressed structure to prepare a positive electrode; and (5) drying the positive electrode, wherein the positive electrode active material slurry in the step (1) has a solid content of 50 to 70% by weight.
[0020] In one embodiment of the present invention, the step (1) is a step of mixing the sulfur-carbon composite and the binder in a ratio of 90:10 to 98.5:1.5.
[0021] In one embodiment of the present invention, in step (3), the roll gap of the roll press is 100 to 200 μm.
[0022] In one embodiment of the present invention, the step (5) is a step of drying by heating, and the drying temperature is 40 to 90°C.
[0023] According to a third aspect of the present invention, there is provided a lithium-sulfur battery comprising the above-described positive electrode. Effect of the Invention
[0024] The positive electrode for a lithium-sulfur battery according to the present invention has excellent surface characteristics, which reduces unevenness and prevents non-uniform growth and dendrite formation in the negative electrode, and has excellent adhesive strength due to a bridge-shaped structure between the positive electrode active materials.
[0025] In addition, the method for manufacturing a positive electrode for a lithium-sulfur battery according to the present invention has the advantage of shortening the drying time of the positive electrode, thereby reducing the cost of the drying process during the manufacturing of the positive electrode, and improving the production speed of the positive electrode. [Brief description of the drawings]
[0026] [Figure 1] 1 is a schematic diagram showing a process for producing a positive electrode according to Examples 1 and 2 of the present invention. [Diagram 2] 1 is a photograph of a high solid content positive electrode active material slurry produced in Example 1 of the present invention. [Diagram 3] 1 is a graph showing the drying rate measured according to drying time during the manufacture of positive electrodes according to Example 1 of the present invention and Comparative Examples 1 and 2. [Figure 4] 1 is a graph showing the arithmetic mean surface roughness (Sa) of positive electrodes according to Examples 1 and 2 of the present invention and Comparative Examples 1, 3 to 5. [Diagram 5]1 is a graph showing the maximum height roughness (Sz) of positive electrodes according to Examples 1 and 2 of the present invention and Comparative Examples 1, 3 to 5. [Figure 6] 1 is a graph showing the adhesive strength of positive electrodes according to Example 1 of the present invention and Comparative Examples 1 and 3. [Figure 7] 1 is a SEM image showing the surface of a positive electrode according to Example 1 of the present invention. [Figure 8] 1 is a graph showing the initial capacity of lithium-sulfur batteries according to Example 3 of the present invention and Comparative Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The embodiments provided by the present invention can all be achieved by the following description. The following description should be understood as describing preferred embodiments of the present invention, and it should be understood that the present invention is not necessarily limited thereto.
[0028] Positive electrodes for lithium-sulfur batteries In the positive electrode for a lithium-sulfur battery according to the present invention, the positive electrode active material layer includes a positive electrode active material and a binder, and the positive electrode active material layer includes the following S a (arithmetic mean surface roughness of positive electrode), S z A cathode for a lithium-sulfur battery having surface properties defined by (maximum height roughness of the cathode).
[0029] (i) 1 μm≦S a ≦5μm (ii) 10 μm≦S z ≦60μm (S a is the average distance from the middle surface of the uneven structure on the positive electrode surface to the highest and lowest points of each uneven portion, and z means the distance from the lowest point to the highest point of the positive electrode)
[0030] As used herein, the S of the positive electrode active material layer a (arithmetic mean surface roughness of positive electrode) and Sz (Maximum height roughness of positive electrode) can be measured based on the ISO 25178 (Geometric Product Specifications (GPS)-Surface texture:areal) standard.
[0031] According to the above standard, S a (arithmetic mean surface roughness of positive electrode) can be defined as follows:
[0032]
number
[0033] (In the above formula 1, S a is the arithmetic mean surface roughness of the positive electrode, A is the measured area, and z(x, y) is the height profile.
[0034] According to the above standard, S z (Positive electrode maximum height roughness) can be defined as follows:
[0035]
number
[0036] (In the above formula 2, S z is the maximum height roughness of the positive electrode, and z(x, y) is the height profile)
[0037] S of the positive electrode active material layer aThe arithmetic mean surface roughness of the positive electrode may be 1 μm or more, 1.5 μm or more, 2 μm or more, 2.5 μm or more, 3 μm or more, 3.5 μm or more, or 4 μm or more, and may be 5 μm or less, 4.9 μm or less, 4.8 μm or less, 4.7 μm or less, 4.6 μm or less, or 4.5 μm or less. If it is less than 1 μm, the surface area may be too small, causing a problem of reduced reactivity of the positive electrode active material. On the other hand, if it exceeds 5 μm, the positive electrode may have large irregularities, which may induce uneven growth of the negative electrode, and may cause stability-related problems such as short circuits and fires inside the battery due to the formation of dendrites.
[0038] S of the positive electrode active material layer z The maximum height roughness of the positive electrode may be 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, or 50 μm or more, and may be 60 μm or less, 59 μm or less, 58 μm or less, 57 μm or less, 56 μm or less, or 55 μm or less. If it is less than 10 μm, the surface area may be too small, causing a problem of reduced reactivity of the positive electrode active material. On the other hand, if it exceeds 60 μm, the unevenness of the positive electrode is formed to a large extent, which may induce uneven growth of the negative electrode, and the formation of dendrites may cause stability-related problems such as short circuits and fires inside the battery.
[0039] The adhesive strength between the current collector and the positive electrode active material layer may be 6.5 gf / cm or more, 7 gf / cm or more, or 7.5 gf / cm or more, or 9.5 gf / cm or less, 9 gf / cm or less, 8.5 gf / cm or less, or 8 gf / cm or less. Referring to the SEM image of Fig. 7, when the above range is satisfied, the binder is not completely dissolved in the positive electrode active material slurry, so a bridging bond type structure is formed between the positive electrode active material particles, improving the adhesive strength between the positive electrode active materials, and thus providing excellent positive electrode adhesive strength.
[0040] The porosity of the positive electrode may be 50% or more, 55% or more, or 60% or more, or 80% or less, 75% or less, or 70% or less. If it is less than 50%, the mass transfer resistance increases when applied to a battery, and the capacity of the electrode may decrease. If it is more than 80%, the energy density per volume of the battery may decrease excessively.
[0041] The positive electrode for the lithium-sulfur battery includes a current collector and a positive electrode active material layer formed on at least one surface of the current collector.
[0042] The current collector is not particularly limited as long as it supports the positive electrode active material, does not cause chemical changes in the battery, and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, palladium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.
[0043] The current collector may have fine irregularities on its surface to strengthen the bonding force with the positive electrode active material, and may be in various forms such as a film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.
[0044] The positive electrode active material layer includes a positive electrode active material and a binder.
[0045] The positive electrode active material may include a material selected from the group consisting of elemental sulfur, a sulfur-based compound, a sulfur-carbon composite, and combinations thereof, and preferably includes a sulfur-carbon composite.
[0046] Since sulfur contained in the positive electrode active material does not have electrical conductivity by itself, it may be used in combination with a conductive material such as a carbon material, and thus the sulfur may be included in the form of a sulfur-carbon composite.
[0047] The sulfur loading of the positive electrode is 1 to 10 mAh / cm 2 , preferably 2 to 8 mAh / cm 2 , more preferably 3 to 6 mAh / cm 2 It is.
[0048] The carbon contained in the sulfur-carbon composite is a porous carbon material, which provides a skeleton to which the sulfur can be uniformly and stably fixed, and complements the low electrical conductivity of sulfur to facilitate electrochemical reactions.
[0049] The porous carbon material can be generally prepared by carbonizing various carbon precursors. The porous carbon material contains non-uniform pores, the average diameter of the pores is in the range of 1 to 200 nm, and the porosity or void ratio is in the range of 10 to 90% of the total volume of the porous carbon material. If the average diameter of the pores is less than the range, the size of the pores is merely at the molecular level, making it impossible to impregnate with sulfur, and conversely, if the average diameter of the pores is more than the range, the mechanical strength of the porous carbon material is weakened, making it unsuitable for use in the manufacturing process of electrodes.
[0050] The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular or bulk-like, and any shape commonly used in lithium-sulfur batteries may be used without limitation.
[0051] The porous carbon material may be any material commonly used in the art that has a porous structure or a high specific surface area. For example, the porous carbon material may be at least one selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), graphite such as natural graphite, artificial graphite, and expanded graphite, and activated carbon, but is not limited thereto.
[0052] The method for producing the sulfur-carbon composite is not particularly limited in the present invention, and any method commonly used in the art may be used.
[0053] In addition to the positive electrode active material, the positive electrode may further include one or more additives selected from a transition metal element, a Group IIIA element, a Group IVA element, sulfur compounds of these elements, and alloys of these elements with sulfur.
[0054] The transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, or Hg, the IIIA group elements may include Al, Ga, In, or Ti, and the IVA group elements may include Ge, Sn, or Pb.
[0055] The binder supports the positive electrode active material on the current collector and organically connects the positive electrode active materials to enhance the binding strength therebetween, and any binder known in the art may be used.
[0056] For example, the binder may include a member selected from the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylpyrrolidone, styrene butadiene rubber, acrylonitrile-butadiene rubber, styrene-isoprene rubber, carboxymethyl cellulose, and combinations thereof.
[0057] It can also contain Li-CMC (Lithium Carboxymethyl Cellulose), which is carboxymethyl cellulose with lithium ions substituted for it, as a binder. Carboxymethyl cellulose (CMC) has the risk of explosion due to hydrogen gas generated by the hydrogen ions contained in the carboxyl groups when the battery is running, and hydrogen ions (H + ) instead of sodium ion (Na + In the case of Na-CMC (sodium carboxymethyl cellulose) where Li is substituted, the lifespan characteristics may be reduced due to sodium ions, whereas when Li-CMC is used as a binder, it shows relatively excellent stability and improved lifespan characteristics.
[0058] The positive electrode active material layer may further include a conductive material.
[0059] The conductive material is a material that electrically connects the electrolyte and the positive electrode active material and serves as a path through which electrons move from a current collector to the positive electrode active material, and any conductive material may be used.
[0060] For example, the conductive material may be graphite such as natural graphite or artificial graphite; carbon black such as Super-P, Denka Black, acetylene black, Ketjen Black, channel black, furnace black, lamp black, or thermal black; carbon derivatives such as carbon nanotubes or fullerene; conductive fibers such as carbon fibers or metal fibers; carbon fluoride; metal powders such as aluminum or nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene, or polypyrrole, which may be used alone or in combination.
[0061] The positive electrode active material slurry for forming the positive electrode active material layer may further include a solvent.
[0062] The solvent may be one that can uniformly disperse the positive electrode active material, the conductive material, and the binder. As such a solvent, water is most preferred as an aqueous solvent, and the water may be distilled water or deionized water. However, the solvent is not necessarily limited thereto, and if necessary, a lower alcohol that can be easily mixed with water may be used. The lower alcohol may be methanol, ethanol, propanol, isopropanol, butanol, etc., and preferably, these may be mixed with water.
[0063] Method for producing positive electrodes for lithium-sulfur batteries The method for producing a positive electrode for a lithium-sulfur battery according to the present invention comprises the steps of: (1) mixing a sulfur-carbon composite and a binder, and then adding water to prepare a positive electrode active material slurry; (2) placing the positive electrode active material slurry on a current collector and covering it with a release film to prepare a structure in the order of current collector-slurry-release film; (3) compressing the structure using a roll press; (4) removing the release film from the compressed structure to prepare a positive electrode; and (5) drying the positive electrode. In the step (1), the positive electrode active material slurry has a solid content of 50 to 70% by mass.
[0064] The method for preparing a positive electrode for a lithium-sulfur battery includes: (1) mixing a sulfur-carbon composite with a binder, and then adding water to prepare a positive electrode active material slurry.
[0065] In step (1), the sulfur-carbon composite and the binder are mixed in a ratio of 90:10 to 98.5:1.5, preferably 93:7 to 98:2, and more preferably 96:4 to 97.5:2.5. If the ratio is less than this range, the cathode active material slurry does not fall off the release film, which may cause a problem in manufacturing the cathode. On the other hand, if the ratio is more than this range, the cathode active material layer may be detached from the current collector due to a low binder content.
[0066] The step (1) of preparing the positive active material slurry may further include adding a conductive material to the mixture of the sulfur-carbon composite and the binder. Specifically, the sulfur-carbon composite, the binder, and the conductive material may be mixed together, and water may be added to prepare the positive active material slurry.
[0067] The conductive material is a material that electrically connects the electrolyte and the positive electrode active material and serves as a path through which electrons move from a current collector to the positive electrode active material, and any conductive material may be used.
[0068] For example, the conductive material may be graphite such as natural graphite or artificial graphite; carbon black such as Super-P, Denka Black, acetylene black, Ketjen Black, channel black, furnace black, lamp black, or thermal black; carbon derivatives such as carbon nanotubes or fullerene; conductive fibers such as carbon fibers or metal fibers; carbon fluoride; metal powders such as aluminum or nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene, or polypyrrole, which may be used alone or in combination.
[0069] As used herein, solids concentration is defined as the mass fraction of solid material in a slurry mixture excluding the solvent.
[0070] The solid content of the positive electrode active material slurry prepared by mixing the sulfur-carbon composite and the binder and then adding water may be 50% by weight or more, 52% by weight or more, 54% by weight or more, 56% by weight or more, or 58% by weight or more, and may be 70% by weight or less, 68% by weight or less, 66% by weight or less, 64% by weight or less, or 62% by weight or less. If the solid content is less than 50% by weight, the drying time may be extended and the production rate of the positive electrode may be reduced. On the other hand, if the solid content is more than 70% by weight, the adhesive strength of the positive electrode active material slurry may be reduced, which may cause difficulties in manufacturing the positive electrode.
[0071] The method for manufacturing a positive electrode for a lithium-sulfur battery includes the step of (2) disposing the positive electrode active material slurry on a current collector, and then covering the current collector with a release film to manufacture a structure in the order of current collector-slurry-release film.
[0072] The release film is intended to prevent the positive electrode active material slurry from sticking to a roll during a roll press process for squeezing, and may be a release film made of polyethylene terephthalate (PET), polypropylene (PP), high density polyethylene (HDPE), or low density polyethylene (LDPE), and preferably may be a release film in which silicone or a fluorine-based hydrophobic material is coated on the polymer material, but is not particularly limited thereto.
[0073] The method for preparing the positive electrode for a lithium-sulfur battery includes (3) compressing the structure using a roll press.
[0074] The current collector-slurry-release film structure is passed through a roll press to compress the positive electrode active material slurry having a high solid content with the rolls, thereby forming a positive electrode having a uniform thickness. The roll press may be composed of two parallel rolls, and the loading of the positive electrode to be manufactured can be adjusted by adjusting the distance between the rolls, i.e., the roll gap.
[0075] In the pressing step using the roll press, the roll gap may be 100 μm or more, 115 μm or more, 130 μm or more, or 145 μm or more, or 200 μm or less, 185 μm or less, 170 μm or less, or 155 μm or less. If the roll gap is less than 100 μm, the cathode may not be formed with a uniform thickness due to the cathode active material contained in the cathode active material slurry having particles larger than the roll gap. On the other hand, if the roll gap is more than 200 μm, the cathode may have an excessively high loading, which may cause cracks and detachment on the surface of the cathode to become severe.
[0076] The method for preparing a positive electrode for a lithium-sulfur battery includes the step of: (4) removing the release film from the pressed structure to produce a positive electrode.
[0077] Since the positive electrode active material slurry is spread to a uniform thickness through the compression process using the roll press to form a positive electrode, it is necessary to remove the release film before the final drying process. If the release film is not removed, the heating and drying time increases, which not only increases the cost of the drying process but also reduces the production speed of the positive electrode manufacturing process.
[0078] The method for preparing a positive electrode for a lithium-sulfur battery may include (5) drying the positive electrode.
[0079] The step (5) is a step of heating and drying the positive electrode active material slurry to remove moisture, and preferably, the positive electrode active material slurry can be dried by heating in an oven. The moisture in the positive electrode active material slurry can be removed by the drying, and finally, a positive electrode can be manufactured.
[0080] In step (5), the drying temperature may be 40° C. or more, 45° C. or more, or 50° C. or more, or 90° C. or less, 85° C. or less, or 80° C. or less. If the drying temperature is less than 40° C., the drying time of the positive electrode is extended, making it difficult to obtain the effects of reducing the cost of the drying process and improving the positive electrode production rate due to the reduced drying time. On the other hand, if the drying temperature exceeds 90° C., sulfur in the positive electrode active material is sublimated, causing a problem of reduced loading of the positive electrode.
[0081] Lithium-sulfur battery The lithium-sulfur battery according to the present invention may include a positive electrode; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.
[0082] The positive electrode is in accordance with what has been described herein before.
[0083] The negative electrode may include a negative electrode current collector and a negative electrode active material layer coated on one or both sides of the negative electrode current collector, or the negative electrode may be a lithium metal plate.
[0084] The negative electrode current collector is for supporting the negative electrode active material layer, and is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and may be selected from the group consisting of copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver, and the alloy may be an aluminum-cadmium alloy, or may be a non-conductive polymer surface-treated with a conductive material, or a conductive polymer. In general, a copper thin plate is used for the negative electrode current collector.
[0085] In addition, the material may be in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, or the like, with or without fine irregularities on the surface.
[0086] The negative active material layer may include a conductive material, a binder, etc. in addition to the negative active material. In this case, the conductive material and the binder are the same as those described above.
[0087] The negative electrode active material is lithium (Li + The lithium-containing compound may include a material capable of reversibly intercalating or deintercalating lithium ions, a material capable of reversibly reacting with lithium ions to form a lithium-containing compound, lithium metal, or a lithium alloy.
[0088] The lithium ion (Li + The material capable of reversibly inserting or de-inserting lithium ions (Li) is, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound is, for example, tin oxide, titanium nitride, or silicone. The lithium alloy is, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0089] Preferably, the negative electrode active material is lithium metal, specifically in the form of a lithium metal thin film or lithium metal powder.
[0090] The method for forming the negative electrode active material is not particularly limited, and may be a layer or film forming method commonly used in the art, such as squeezing, coating, deposition, etc. In addition, the negative electrode of the present invention may include a case where a thin lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on a current collector.
[0091] The electrolyte is not particularly limited as long as it is a non-aqueous solvent that serves as a medium through which ions involved in the electrochemical reaction of the battery can move. For example, the solvent may be a carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvent. Specific examples of the carbonate-based solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). Specific examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, 1,1-dimethylethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, and caprolactone. Specific examples of the ether solvent include diethyl ether, dipropyl ether, dibutyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, diglyme, triglyme, tetraglyme, tetrahydrofuran, 2-methyltetrahydrofuran, and polyethylene glycol dimethyl ether. Specific examples of the ketone solvent include cyclohexanone. Specific examples of the alcohol solvent include ethanol and isopropyl alcohol. The aprotic solvent may be, for example, a nitrile such as acetonitrile, an amide such as dimethylformamide, a dioxolane such as 1,3-dioxolane (DOL), or sulfolane. The non-aqueous organic solvent may be used alone or in combination, and the mixing ratio of the non-aqueous organic solvents may be adjusted according to the desired battery performance. In particular, a 1:1 volumetric mixture of 1,3-dioxolane and dimethoxyethane is preferred.
[0092] The electrolyte injection can be performed at an appropriate stage during the manufacturing process of the lithium-sulfur battery depending on the manufacturing process and the required properties of the final product, i.e., before or at the final stage of assembly of the lithium-sulfur battery.
[0093] A conventional separator may be interposed between the positive electrode and the negative electrode. The separator is a physical separator having a function of physically separating the electrodes, and may be any separator that is commonly used, and is particularly preferred to have low resistance to ion transfer in the electrolyte and excellent moisture absorption capacity for the electrolyte.
[0094] In addition, the separator separates or insulates the positive electrode and the negative electrode from each other and allows lithium ions to be transported between the positive electrode and the negative electrode, and may be made of a porous non-conductive or insulating material. The separator may be any material that is generally used as a separator in a lithium-sulfur battery, and may be used without any particular limitation. The separator may be an independent member such as a film, or may be a coating layer added to the positive electrode and / or the negative electrode.
[0095] The separator may be made of a porous substrate. The porous substrate may be any porous substrate typically used in lithium-sulfur batteries. A porous polymer film may be used alone or in combination. For example, a nonwoven fabric or polyolefin-based porous membrane made of high-melting-point glass fiber, polyethylene terephthalate fiber, or the like may be used, but is not limited thereto.
[0096] The material of the porous substrate is not particularly limited in the present invention, and any porous substrate generally used in lithium-sulfur batteries may be used. For example, the porous substrate may be a polyolefin such as polyethylene or polypropylene, a polyester such as polyethyleneterephthalate or polybutyleneterephthalate, a polyamide, a polyacetal, a polycarbonate, a polyimide, a polyetheretherketone, a polyethersulfone, a polyphenyleneoxide, a polyphenylenesulfide, a polyethylenenaphthalate, a polytetrafluoroethylene, a polyvinylidene fluoride, a polyvinyl chloride, or the like. The material may include one or more materials selected from the group consisting of poly(p-phenylene benzobisoxazole), polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobisoxazole), and polyarylate.
[0097] The thickness of the porous substrate is not particularly limited, but is 1 to 100 μm, preferably 5 to 50 μm. The thickness range of the porous substrate is not limited to the above range, but if the thickness is smaller than the above lower limit, the mechanical properties are deteriorated and the separator is easily damaged during use of the battery.
[0098] The average diameter of the pores in the porous substrate and the porosity are not particularly limited, but are in the range of 0.1 to 50 μm and 10 to 95%, respectively.
[0099] The lithium-sulfur battery according to the present invention can be manufactured by laminating (stack) and folding processes of the separator and electrodes in addition to the general winding process.
[0100] The shape of the lithium-sulfur battery is not particularly limited, and may be in various shapes such as a cylindrical shape, a laminated shape, a coin shape, and the like.
[0101] In the following, preferred examples are presented to facilitate understanding of the present invention. However, the following examples are provided merely to facilitate understanding of the present invention, and the present invention is not limited thereto.
[0102] Preparation of Positive Electrodes for Lithium-Sulfur Batteries: Examples 1-2 and Comparative Examples 1-5 [Example 1] 97% by weight of sulfur-carbon composite (S:C=70:30 (weight ratio)) and 3% by weight of Li-CMC (Lithium-Carboxymethyl Cellulose), a solid powder binder, were mixed, and water was added to prepare a positive electrode active material slurry with a solid content of 60% by weight.
[0103] The prepared positive electrode active material slurry was placed on one side of an aluminum current collector, and then a PET release film (Mitsubishi, MRF-125, thickness 125 μm) was placed on the slurry to prepare a current collector-slurry-release film structure. Then, the structure was placed in a roll press and pressed while adjusting the roll gap to 120 μm.
[0104] After squeezing, the release film was removed from the structure, and the structure was placed in an oven and dried at 50°C to obtain a structure with a porosity of 63% and a sulfur loading of 3.65mAh / cm. 2A positive electrode having the formula:
[0105] [Example 2] A sulfur-carbon composite (S:C=75:25), carbon fiber as a conductive material, and Li-CMC (Lithium-Carboxymethyl Cellulose) as a solid powder binder were mixed in a mass ratio of 92:5:3, and water was added to prepare a positive electrode active material slurry with a solid content of 55% by mass.
[0106] A positive electrode was manufactured in the same manner as in Example 1 except for the manufacturing method of the positive electrode active material slurry. The positive electrode had a porosity of 63% and a sulfur loading of 3.4 mAh / cm 2 A positive electrode having the formula:
[0107] [Comparative Example 1] A sulfur-carbon composite (S:C = 70:30 (mass ratio)) and a 2 wt% Li-CMC (lithium carboxymethyl cellulose) aqueous solution as a binder were mixed so that the mass ratio of the sulfur-carbon composite to the Li-CMC solids was 97:3, and then water was added to prepare a cathode active material slurry with a solids concentration of 30 mass%.
[0108] Thereafter, the positive electrode active material slurry was coated on one side of an aluminum current collector using a blade coater (Mathis Switzerland, SV-M) and dried in an oven at 50° C., and a positive electrode for a lithium-sulfur battery was manufactured in the same manner as in Example 1, and the porosity of the manufactured positive electrode was 78%.
[0109] [Comparative Example 2] A positive electrode for a lithium-sulfur battery was prepared in the same manner as in Example 1, except that the release film was not removed and the positive electrode was dried by heating.
[0110] [Comparative Example 3] The positive electrode prepared in Comparative Example 1 was put into a roll press and an additional pressing process was performed while adjusting the roll gap to 50 μm to prepare a positive electrode for a lithium-sulfur battery. The porosity of the positive electrode prepared at this time was 63%.
[0111] [Comparative Example 4] A sulfur-carbon composite (S:C = 75:25 (mass ratio)), carbon fiber as a conductive material, and a 2 wt% Li-CMC (Lithium Carboxymethyl Cellulose) aqueous solution as a binder were mixed to a mass ratio of 92:5:3, and then water was added to prepare a cathode active material slurry with a solid content of 30 mass%.
[0112] A positive electrode was manufactured in the same manner as in Comparative Example 1, except for the manufacturing method of the positive electrode active material slurry. The positive electrode had a porosity of 69% and a sulfur loading of 3.4 mAh / cm 2 A positive electrode having the formula:
[0113] [Comparative Example 5] The positive electrode prepared in Comparative Example 4 was put into a roll press and an additional pressing process was performed while adjusting the roll gap to 50 μm to prepare a positive electrode for a lithium-sulfur battery. The porosity of the positive electrode thus prepared was 63%.
[0114] Fabrication of Lithium-Sulfur Battery: Example 3 and Comparative Example 6 [Example 3] The positive electrode prepared in Example 2 and a negative electrode made of lithium metal with a thickness of 45 μm were placed facing each other, and a polyethylene separator with a thickness of 20 μm and a porosity of 46% was interposed between the positive electrode and the negative electrode.
[0115] In addition, the electrolyte solvent was 1,3-dioxolane (DOL) / dimethoxyethane (DME) (1:1, v / v), and 1M LiTFSI and 3% by mass of lithium nitrate (LiNO3) were injected to fabricate a coin cell type lithium-sulfur battery.
[0116] [Comparative Example 6] A coin cell type lithium-sulfur battery was manufactured in the same manner as in Example 3, except that the positive electrode manufactured in Comparative Example 5 was used.
[0117] Experimental example 1: Measurement of drying time during the manufacture of positive electrodes for lithium-sulfur batteries The drying time (min) and drying rate (%) required to remove the solvent from the positive electrode active material slurry during the preparation of the positive electrodes in Example 1 and Comparative Examples 1 and 2 were measured, and the results are shown in FIG.
[0118] Specifically, the drying rate was calculated by measuring the mass of residual moisture over time and using the following formula.
[0119] Drying rate (%) = (1-((mass of residual moisture) / (mass of initial moisture))) x 100
[0120] 3, in Example 1, more than 95% of the solvent in the slurry was removed in 35 minutes, whereas in Comparative Example 1, it took 60 minutes to achieve the same drying rate. Also, in Comparative Example 2, which was dried while covered with a release film, the drying speed was relatively slower compared to Example 1 and Comparative Example 1.
[0121] From the above results, it was confirmed that in Example 1, in which a positive electrode was manufactured by applying a roll press process using a slurry having a solid content of 50 to 70% by weight, the drying time was significantly shortened compared to Comparative Examples 1 and 2.
[0122] Experimental example 2: Surface property measurement of positive electrodes for lithium-sulfur batteries The surface roughness of the positive electrodes prepared in Examples 1 and 2 and Comparative Examples 1, 3 to 5 was measured using a measuring instrument (KEYENCE, VK-X150). a (arithmetic mean height of the positive electrode (average of the distance from the middle surface of the positive electrode surface unevenness structure to the highest and lowest points of each unevenness), S zThe maximum height of the positive electrode (the distance from the lowest point to the highest point of the positive electrode) was measured and shown in Table 1 and FIGS.
[0123] [Table 1]
[0124] As shown in Table 1, in Examples 1 and 2 in which positive electrodes were prepared by a roll press process using a slurry having a high solid content of 50 to 70 wt %, the surface roughness was smaller, the unevenness was smaller, and the surface was flatter than in Comparative Example 1 or Comparative Examples 3 to 5 in which positive electrodes were prepared using a slurry having a low solid content.
[0125] Through this, it was found that the cathodes prepared in Examples 1 and 2 had relatively small surface irregularities, which prevented the uneven growth of the anode and the formation of dendrites, thereby improving the stability of the battery.
[0126] Experimental Example 3: Adhesion Measurement of Positive Electrodes for Lithium-Sulfur Batteries The positive electrodes prepared in Example 1 and Comparative Examples 1 and 3 were cut to a size of 100 mm x 20 mm, and the electrode surface was attached to a slide glass using double-sided tape (3M 9070), and a sample for a peel test was prepared using a laminator (GMP, PHOTONEX-SYNC325).
[0127] The peel test samples were subjected to a 90° peel test using a universal testing machine (AMETEK, LS1) capable of measuring adhesive strength, and the applied peel resistance (gf / cm) was measured to calculate the adhesive strength of each electrode. The results are shown in Table 2 and FIG. 6.
[0128] [Table 2]
[0129] FIG. 7 shows an image of the positive electrode active material of Example 1 taken with a scanning electron microscope (SEM) (JEOL, JSM-7200F).
[0130] From the above results, it was confirmed that in the case of a positive electrode active material slurry having a high solid content of 50 to 70 wt% as in Example 1, the active material was not completely dissolved in the binder and had a bridge-shaped structure between the active materials, thereby improving the adhesive strength of the positive electrode.
[0131] Experimental Example 4: Measurement of initial capacity of lithium-sulfur battery For the lithium-sulfur batteries prepared in Example 3 and Comparative Example 6, the initial discharge capacity was measured from 2.5 V to 1.8 V using a charge-discharge measuring device (PESC 05-0.01, PNE Solution, Korea), and the results are shown in FIG.
[0132] From the results of FIG. 8, it was found that in the case of a lithium-sulfur battery including a positive electrode manufactured by a roll press process using a slurry having a high solid content of 50 to 70% by weight as in Example 3, compared to a lithium-sulfur battery in which a positive electrode is manufactured using a slurry having a low solid content as in Comparative Example 6, the drying time in the positive electrode manufacturing process was significantly shortened, thereby reducing the cost of the drying process, and the positive electrode production rate was improved, while still showing the same level of initial capacity.
[0133] Any simple modifications or variations of the present invention are within the scope of the present invention, and the specific scope of protection of the present invention will be defined by the appended claims.
Claims
1. (1) mixing the sulfur-carbon composite and a binder, and then adding water to prepare a positive electrode active material slurry; (2) placing the positive electrode active material slurry on a current collector and covering it with a release film to prepare a structure in the order of current collector-slurry-release film; (3) compressing the structure using a roll press; (4) removing the release film from the pressed structure to produce a positive electrode; and (5) drying the positive electrode; In the step (1), the solid content of the positive electrode active material slurry is 50% by weight to 70% by weight.
2. 2. The method of claim 1, wherein the step (1) comprises mixing the sulfur-carbon composite and the binder in a ratio of 90:10 to 98.5:1.
5.
3. 2. The method of claim 1, wherein in the step (3), a roll gap of the roll press is 100 μm to 200 μm.
4. 4. The method of claim 1, wherein the step (5) is a step of drying by heating, and the drying temperature is 40° C. to 90° C.
Citation Information
Patent Citations
Electrode body and electric storage device
JP2019021805A
Manufacturing method of electrode for lithium ion battery and manufacturing method of lithium ion battery
JP2019125499A
Electrode and lithium secondary battery comprising same
WO2019009560A1
Binder, and electrode and lithium secondary battery comprising same
WO2019078505A1
Cathode slurry composition, cathode manufactured using same, and battery including same
WO2019139397A1